17% Efficient Organic Solar Cells Based on Liquid Exfoliated WS2 as a Replacement for PEDOT:PSS. Issue 46 (30th September 2019) - Lin, Yuanbao; Adilbekova, Begimai; Firdaus, Yuliar; Yengel, Emre; Faber, Hendrik; Sajjad, Muhammad; Zheng, Xiaopeng; Yarali, Emre; Seitkhan, Akmaral; Bakr, Osman M.; El‐Labban, Abdulrahman; Schwingenschlögl, Udo; et al.
Abstract: The application of liquid‐exfoliated 2D transition metal disulfides (TMDs) as the hole transport layers (HTLs) in nonfullerene‐based organic solar cells is reported. It is shown that solution processing of few‐layer WS2 or MoS2 suspensions directly onto transparent indium tin oxide (ITO) electrodes changes their work function without the need for any further treatment. HTLs comprising WS2 are found to exhibit higher uniformity on ITO than those of MoS2 and consistently yield solar cells with superior power conversion efficiency (PCE), improved fill factor (FF), enhanced short‐circuit current ( J SC ), and lower series resistance than devices based on poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) and MoS2 . Cells based on the ternary bulk‐heterojunction PBDB‐T‐2F:Y6:PC71 BM with WS2 as the HTL exhibit the highest PCE of 17%, with an FF of 78%, open‐circuit voltage of 0.84 V, and a J SC of 26 mA cm −2 . Analysis of the cells' optical and carrier recombination characteristics indicates that the enhanced performance is most likely attributed to a combination of favorable photonic structure and reduced bimolecular recombination losses in WS2 ‐based cells. The achieved PCE is the highest reported to date for organic solar cells comprised of 2D charge transport interlayers and highlights the potential of TMDs as inexpensive HTLs for high‐efficiency organic photovoltaics. Abstract : The use of liquid exfoliated 2D WS2 and MoS2 as hole‐transporting layers (HTLs) in ultrahigh efficiency organic solar cells is reported. WS2 yields cells with higher power conversion efficiency (PCE), fill‐factor, and short‐circuit current than MoS2 and poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate). When WS2 is introduced as HTL in PBDB‐T‐2F:Y6:PC71 BM organic solar cells, a maximum PCE value of 17% is achieved.